Public perceptions and lightning safety education in Sri Lanka - Jayaratne, Chandana; Gomes, Chandima (IEEE, 2012)
Sri Lanka, a tropical island in the Indian Ocean, experiences relatively high density of lightning. The island has a record of lightning research and lightning education programs that dates back to several decades. Lightning research in the country has a number of measurable outcomes; however, there are no indicators to evaluate the success rate of awareness programs. This paper summarizes the activities pertinent to lightning research and education carried out in the country so far and analysis of information gathered during the recent times on public opinion on various critical safety and protection issues. Consequently, based on the outcome of analysis new modalities are proposed for countries with similar lightning density and social structure to launch lightning education programs with success.